Elimination of Arsenophonus increases susceptibility to sulfoxaflor in Aphis gossypii - Alimu, Abulaiti; Zhong, Xiao; Gao, Yu; Lu, Yanhui (Frontiers in Microbiology, 2026)
IntroductionThe cotton aphid, Aphis gossypii Glover, is a globally significant agricultural pest that harbors diverse microbial symbionts. Beyond their well-known roles in nutrition, these microbial partners are increasingly recognized for their potential to modulate host detoxification pathways and influence insecticide susceptibility. While sulfoxaflor is a primary insecticide for controlling A. gossypii, the extent to which the predominant secondary symbiont, Arsenophonus, mediates susceptibility to this chemical remains largely unexplored.MethodsIn this study, we investigated the role of Arsenophonus in modulating host sulfoxaflor susceptibility and the underlying molecular mechanisms. We established an Arsenophonus-infected A. gossypii line (A-infected) and an antibiotic-cured, Arsenophonus-deleted line (A-deleted). To ensure identical genetic backgrounds and eliminate residual antibiotic effects, the A-deleted line was maintained for 10 generations under antibiotic-free conditions, with symbiont status confirmed by PCR and 16S rRNA sequencing. We then compared sulfoxaflor susceptibility, analyzed protein levels of detoxification enzymes, performed comparative transcriptomic analysis, and validated key candidate genes using RNA interference (RNAi).Results and discussionBioassays revealed that the elimination of Arsenophonus significantly increased susceptibility to sulfoxaflor. This hypersensitivity was metabolically associated with reduced protein levels of mixed-function oxidases (MFOs) and glutathione S-transferases (GSTs). Comparative transcriptomic analysis identified multiple differentially expressed cytochrome P450 genes, including CYP380C44, CYP380C45, CYP6J1, CYP6CY14, CYP6CY21, CYP4CJ1, and CYP4C1. Functional verification demonstrated that RNAi-mediated silencing of CYP380C44 in the A-infected line significantly increased sulfoxaflor mortality. Collectively, our findings demonstrate that the secondary symbiont Arsenophonus modulates the host response to sulfoxaflor by regulating P450-mediated metabolic pathways. Identifying CYP380C44 as a critical effector gene highlights the Arsenophonus-P450 axis as a potential molecular target for developing novel pest control strategies that exploit symbiotic vulnerabilities